Ex-ante labor market effects of compulsory military service - Torun, Huzeyfe (Journal of Comparative Economics, 2019)
•Coonscription affects labor market outcomes of potential conscripts before the service.•Abolition of conscription in Spain increased the LFP of teenage men by 6.7%.•Abolition of conscription decreased the LFP of teenage women.•LFP rate of teenage men is significantly lower in countries with conscription. Previous research on military conscription exclusively focuses on the effect of military service on subsequent labor market outcomes. I examine the effect of peacetime conscription on early labor market outcomes of potential conscripts before they are called up for service. In the first part, I exploit the abolition of conscription in Spain as a natural experiment. In a difference-in-differences framework, I show that the abolition of conscription in Spain increased the labor force participation of teenage men by 6.7% compared to men in their twenties, and employment by 11%, while reducing unemployment in this group by 9%. Interestingly, I find opposite effects on teenage women in Spain who are not subject to conscription suggesting high degree of substitutability between young men and women in the labor market. I also point out that although the labor force participation rates of men in their twenties are quite similar across Turkey, Peru and Argentina, that of teenage men is significantly lower in Turkey, which has compulsory military service.